Conflicts in policy objectives : papers presented to Section F (Economics) at the 1970 Annual Meeting of the British Association for the Advancement of Science - British Association for the Advancement of Science; Kaldor, Nicholas (Oxford, England : Basil Blackwell, 1971)
The first paper in this volume deals with the post-war policies of demand management for full employment which had their origin in the Government White Paper on Employment Policy in 1944, and its implications on various policy objectives such as economic growth, monetary stability and the balance of payments. Conflicts in the field of social security policy are examined in paper two. Paper three examines recent criticisms concerning the desirability of the growth objective as such. Papers four through five look at major policy conflicts as seen from the angle of the low-income countries, particularly the conflict between the growth wages and productivity and the level employment. Papers six, seven, and eight discuss the relationship between economic growth and inflation, the problem of regional economic growth, and the growth and the balance of payments respectively.
Includes bibliographical references.
ne 28/06/2018
Loans
Keywords: Economic policy; Economic development; Great Britain